2018
DOI: 10.1590/1982-02752018000300007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early childhood education attendance on achievement, social skills, behaviour, and stress

Abstract: There is evidence that Early Childhood Education positively contributes to optimal performance in Elementary School, but there are few studies about its infl uence on socio-behavioral variables. This study aimed to explore the association between duration of Early Childhood Education attendance (one or two years) and developmental outcomes in the 3rd grade. A total of 151 students from public schools participated in the study and their academic performance, social skills, externalizing behavior and stress symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
3
0
5
Order By: Relevance
“…Dos seis artigos selecionados, os artigos 1 e 6 (33,2%) 3,17 estavam no idioma inglês e os artigos 2,3,4 e 5 (66,4%) [13][14][15][16] , no idioma português, nenhum em espanhol.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Dos seis artigos selecionados, os artigos 1 e 6 (33,2%) 3,17 estavam no idioma inglês e os artigos 2,3,4 e 5 (66,4%) [13][14][15][16] , no idioma português, nenhum em espanhol.…”
Section: Resultsunclassified
“…Em relação à base de dados, os artigos 2,3,4 e 5 (66,4%) [13][14][15][16] foram indexados na LILACS; o artigo 6 (16,6%) 17 na SciELO e o artigo1 (16,6%) 3 na base MEDLINE.…”
Section: Resultsunclassified
“…Previous studies have shown that the relationship between academic achievement and preschool attendance decreases when the effect of socioeconomic level is controlled (Correia-Zanini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The dissemination of preschool education has become a global education goal to maximize students' high learning capacity during this period (OECD, 2020). However, in countries where preschool education is not compulsory and is still expanding, children from socioeconomically advantaged families attend education at this level more frequently than their peers with lower SES (Bassok et al, 2016;Correia-Zanini et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation